IDENTIFIKASI POSTUR KERJA PENGRAJIN BATIK JUMPUTAN DENGAN METODE JOB STRAIN INDEX (JSI) - Patradhiani, Rurry; Nopriansyah, Beno; Hastarina, Merisha (Inaque : Journal of Industrial and Quality Engineering, 2021)
UKM Batik Jumputan Ishak Palembang is one of the UKM that produces batik jumputan. Where all activities in the process of making batik jumputan are done manually by sitting and standing for a long time. These activities can pose a risk of injury to workers. The purpose of this study is to determine the level of ergonomic risk in jumputan batik workers and provide recommendations for improvement from the results of measuring the level of ergonomic risk in jumputan batik craftsmen. Ergonomics risk level assessment uses the Job Strain Index (JSI) method, where the JSI method uses six parameters, namely the intensity of effort use, duration of energy use, number of efforts per minute, hand position, work speed, and duration of activity per day. The results of the assessment show that the level of ergonomics risk based on the JSI method is that there are 7 work activities at a low risk level or the worker is safe with a JSI score 3, and there are 2 work activities at a moderate risk level with a JSI score 7, namely these activities have the potential to pose a work risk where activities that fall into the moderate risk category are the process of tasting cloth and picking cloth. For the improvement of work in the jumputan batik production process, additional work facilities such as tables and chairs can be provided which in the design consider anthropometric factors, so that the energy used at work can be reduced and can avoid the risk of work accidents. Keyword: Ergonomic Risk, Work Posture, Job Strain Index (JSI)